2010
DOI: 10.1007/s11235-010-9332-0
|View full text |Cite
|
Sign up to set email alerts
|

Options and overbooking strategy in the management of wireless spectrum

Abstract: Dynamic spectrum management makes it possible for the owner of usage rights on some frequency blocks to sublet each of them in real time and for a limited period of time. As a softer implementation with respect to the spot market a two stage assignment is here proposed through the use of options, which give buyers the right to purchase the usage right on a single block and for a timeslot. In the sale of options the primary owner may accomplish an overbooking strategy, which consists in selling more blocks than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Buying such rights on demand could not be possible, because the alternative network is not available, or could prove to be too expensive when the offering party uses its dominant position, taking advantage of the urgent need of the provider having outage problems in its network. A preventive purchase of usage rights is represented by the option for leasing spectrum examined in [58].…”
Section: Market Meansmentioning
confidence: 99%
“…Buying such rights on demand could not be possible, because the alternative network is not available, or could prove to be too expensive when the offering party uses its dominant position, taking advantage of the urgent need of the provider having outage problems in its network. A preventive purchase of usage rights is represented by the option for leasing spectrum examined in [58].…”
Section: Market Meansmentioning
confidence: 99%
“…Additionally, it has been suggested that it is introduced in network design [8,9,29,49,50]. In response to some disadvantages of VaR, especially the lack of subadditivity (see Sect.…”
Section: Probabilistic Risk Measuresmentioning
confidence: 99%